Communication and Democracy: Relationships between Media and Citizenship in Brazil and Germany - Luvizotto, Caroline Kraus [UNESP]; da Costa, Ana Beatriz Lemos; Coelho, Jairo Faria Guedes; Bezerra, Kalianny (Colegio Mayor de Nuestra Senora del Rosario, 2024)
This text addresses the dynamics of Internet access, the accountability of media and public service broadcasting, and media transparency and its implications for the right and access to information and communication, contributing descriptively and reflectively on the relations between media and citizens in the contexts of Brazil and Germany. The methodological path follows the procedures of the literature review and document analysis. The reflection begins with considerations on the Internet access, the challenges related with the convergence of the traditional services and platforming. Next, the accountability of media and public service broadcasting is addressed, from the analyses of the instruments of social participation in the public media companies of both countries. The last aspect discussed in the text demonstrates how the mass media, and more specifically, the news organizations on both countries, articulate transparency resources in their practices. The results suggest that the study of Internet access, media responsibility, and transparency in the contexts of Brazil and German reveals important insights into their impact on the civic participation and the maintenance of democracy.
Comunicación y democracia: relaciones entre los medios y la ciudadanía en Brasil y Alemania
COMUNICAÇÃO E DEMOCRACIA: AS RELAÇÕES ENTRE MÍDIA E CIDADANIA NO BRASIL E NA ALEMANHA
Keywords: Brazil; Communication; democracy; Germany; mass media